Efeitos relativísticos em campos eletromagnéticos de descargas atmosféricas - Silva, Romeu Holanda da (Universidade Federal Rural do Semi-Árido, 2018)
The atmospheric discharges cause many social and economical damages to the humanity and they are not still completely understood by the science. In this monograph, a model is proposed for the current of the return discharge starting from the analysis of the relativistic movement of a loaded particle in a very intense electric field. Starting from the current model he/she is derived analytical expressions for the potencials to climb and vectorial. Finally, using the fundamental equations of the electromagnetism is analytical expressions for the vertical electric field, the radial electric field and the magnetic azimutal around the discharge channel.
Keywords: Eletromagnetismo; Modelo; Relatividade; Descargas atmosféricas; Electromagnetism; Model; Relativity; Atmospheric discharges; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA